1999
DOI: 10.1083/jcb.147.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a-Type Lamin Expression Compromises Nuclear Envelope Integrity Leading to Muscular Dystrophy

Abstract: The nuclear lamina is a protein meshwork lining the nucleoplasmic face of the inner nuclear membrane and represents an important determinant of interphase nuclear architecture. Its major components are the A- and B-type lamins. Whereas B-type lamins are found in all mammalian cells, A-type lamin expression is developmentally regulated. In the mouse, A-type lamins do not appear until midway through embryonic development, suggesting that these proteins may be involved in the regulation of terminal differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
1,221
6
7

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,116 publications
(1,314 citation statements)
references
References 33 publications
62
1,221
6
7
Order By: Relevance
“…The first is a mouse line that does not express lamin A or C proteins (Lmna −/− ). These mice die at 6-7 weeks of age from muscular dystrophy and cardiomyopathy [19]. However, there is no report of a human patient completely lacking lamins A/C, apart from one patient that may have been haploinsufficient for LMNA, due to the presence of a nonsense mutation at codon 6 [9] and a fetus that died late in gestation that was homozygous for a premature stop codon in LMNA [20].…”
Section: The A-type Laminopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is a mouse line that does not express lamin A or C proteins (Lmna −/− ). These mice die at 6-7 weeks of age from muscular dystrophy and cardiomyopathy [19]. However, there is no report of a human patient completely lacking lamins A/C, apart from one patient that may have been haploinsufficient for LMNA, due to the presence of a nonsense mutation at codon 6 [9] and a fetus that died late in gestation that was homozygous for a premature stop codon in LMNA [20].…”
Section: The A-type Laminopathiesmentioning
confidence: 99%
“…Loss of the A-type lamins results in the redistribution of emerin away from the nucleus to the endoplasmic reticulum, suggesting that reduced levels of emerin at the nuclear envelope contribute to the etiology of AD-and X-linked EDMD [19]. Array analysis of regenerating Emd null muscle revealed abnormalities in cell-cycle parameters and delayed myogenic differentiation, which were associated with perturbations to transcriptional pathways regulated by the retinoblastoma (Rb1) and MyoD genes.…”
Section: The A-type Laminopathiesmentioning
confidence: 99%
“…7 Representative cross-sections of hematoxylin and eosinstained EDL, tibialis anterior (TA), soleus, gastrocnemius, quadriceps, and diaphragm muscles from Zmpste24 +/+ and Zmpste24 −/− mice. Scale bar is 50 μm localization of emerin at the nuclear rim (Sullivan et al 1999) (nor elevated serum creatine kinase activity (Emery 2002)). The only histological aberration that we consistently observed was excessive myonuclei in fibers of Zmpste24 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in lamins A and C cause a phenotypically identical but autosomal dominantly inherited form of Emery-Dreifuss muscular dystrophy [Bonne et al, 1999]. Interestingly, lamins A and C and emerin have been shown to interact in vitro and in vivo [Fairley et al, 1999;Sullivan et al, 1999;Clements et al, 2000;Sakaki et al, 2001]. Heterozygous mutations in lamin B receptor cause Pelger-Huët anomaly, a benign alteration of neutrophil nuclear morphology [Hoffmann et al, 2002].…”
Section: Inherited Diseases Caused By Mutations In Inner Nuclear Membmentioning
confidence: 99%
“…Lammerding et al [2004] have shown that fibroblasts from lamin A/C null mice have nuclear structural defects and attenuated NFkappaB-regulated transcription in response to mechanical or cytokine stimulation. Lamin A/C null mice develop cardiomyopathy and skeletal muscle abnormalities similar to human Emery-Dreifuss muscular dystrophy [Sullivan et al, 1999;Nikolova et al, 2004]. Hence, abnormal signal transduction may play a role the development of striated muscle disease with loss of A-type lamins.…”
Section: Concluding Speculationmentioning
confidence: 99%